Caveolin-1 Alleviates Acetaminophen-Induced Fat Accumulation in Non-Alcoholic Fatty Liver Disease by Enhancing Hepatic Antioxidant Ability via Activating AMPK Pathway - Wang, Jiarong; Jiang, Wei; Xin, Jiao; Xue, Weiju; Shi, Congjian; Wen, Jiagen; Huang, Yan; Hu, Chengmu (Frontiers in Pharmacology, 2021)
Non-alcoholic fatty liver disease (NAFLD) is an independent risk factor for acute liver injury caused by overuse of acetaminophen (APAP). Caveolin-1 (CAV1), a regulator of hepatic energy metabolism and oxidative stress, was found to have a protective effect against NAFLD in our previous study. However, it remains unclear whether CAV1 has a protective effect against APAP-induced hepatotoxicity in NAFLD. The aim of this study was to determine whether CAV1 inhibits oxidative stress through the AMPK/Nrf2/HO-1 pathway to protect the liver from fat accumulation exacerbated by APAP in NAFLD. In this study, seven-week-old C57BL/6 male mice (18–20 g) were raised under similar conditions for in vivo experiment. In vitro, L02 cells were treated with A/O (alcohol and oleic acid mixture) for 48h, and APAP was added at 24h for further incubation. The results showed that the protein expression of the AMPK/Nrf2 pathway was enhanced after CAV1 upregulation. The effects of CAV1 on fat accumulation, ROS, and the AMPK/Nrf2 anti-oxidative pathway were reduced after the application of CAV1-siRNA. Finally, treatment with compound C (an AMPK inhibitor) prevented CAV1 plasmid-mediated alleviation of oxidative stress and fat accumulation and reduced the protein level of Nrf2 in the nucleus, demonstrating that the AMPK/Nrf2/HO-1 pathway was involved in the protective effect of CAV1. These results indicate that CAV1 exerted a protective effect against APAP-aggravated lipid deposition and hepatic injury in NAFLD by inhibiting oxidative stress. Therefore, the upregulation of CAV1 might have clinical benefits in reducing APAP-aggravated hepatotoxicity in NAFLD.